Pemanfaatan Sistem Informasi Manajemen Di SMA IT Iqra Kota Bengkulu - Yana Sari, Wira; Nur Sasongko, Rambat (Manajer Pendididikan, 2024)
This research aims to describe the utilization of management information systems in schools, including the utilization of software, hardware, and networks by users. A qualitative research method was chosen, utilizing observation, interviews, and documentation techniques. This research was conducted at SMAIT IQRA in the city of Bengkulu. The informants in this study included the school principal, curriculum coordinator, and school operators. The results of the study indicate that SMAIT IQRA in Bengkulu has implemented the utilization of information systems in the school, including the use of software that is not yet fully integrated. The utilization of hardware and networks by users in the school has been adapted to keep up with developments, collaborating with third parties, and providing training to enhance the teachers' skills.